Impact of chronic monosodium glutamate exposure on female reproductive health in an animal model - Fathunikmah Fathunikmah; Siti Mona Amelia Lestari; Ani Laila; Zahira Abyan Putri Wahyudhi (AcTion: Aceh Nutrition Journal, 2025)
Monosodium glutamate (MSG) is a widely used food additive; however, its chronic effects on female reproductive health remain unclear. Previous studies have mainly focused on neurotoxic and metabolic outcomes, leaving a gap in understanding its impact on ovarian function. This study investigated the effects of chronic MSG exposure on ovarian structure and follicular development in female mice. An experimental post-test-only control group design was used at the Biomedical Laboratory, Poltekkes Kemenkes Riau, Indonesia, from August to October 2024. Twenty-four female Swiss mice (Mus musculus), aged 8–10 weeks and weighing 25–30 g, were randomly divided into four groups (n = 6 per group). The control group received standard feed, while the treatment groups were administered MSG orally at low (0,25 g/kg body weight/day), medium (1 g/kg body weight/day), and high (4 g/kg body weight/day) doses for eight weeks. Ovarian tissues were examined using histopathology and flow cytometry. Data were analyzed using one-way analysis of variance (ANOVA), post-hoc tests, and correlation analysis. The medium- and high-dose groups showed significant reductions in primary (12,3 ± 2,1; 8,7 ± 1,9) and secondary follicles (7,8 ± 1,5; 4,9 ± 1,2), accompanied by tissue degeneration and germ cell apoptosis. A strong negative correlation was observed between MSG dose and mature follicle count (r = –0,72; p < 0,01). In conclusion, these findings demonstrate dose-dependent ovarian impairment, underscoring the need for dietary risk evaluation and increased public awareness regarding excessive MSG consumption.ChE is not strong enough to assess changes in body composition clinically.